MECHANISMS OF ORTHOPYROXENE DISSOLUTION IN SILICA-UNDERSATURATED MELTS AT 1 ATMOSPHERE AND IMPLICATIONS FOR THE ORIGIN OF SILICA-RICH GLASS IN MANTLE XENOLITHS - Shaw C.S.J.; Thibault Y.; Edgar A.D.; Lloyd F.E. (My University, 1998)
Experiments dissolving orthopyroxene (En93) in a variety of Si-undersaturated alkaline melts at 1 atmosphere and variable f O2 demonstrate that orthopyroxene dissolves to form olivine, Si-rich melt and clinopyroxene. These phases form a texturally and chemically distinct boundary layer around the partly dissolved orthopyroxene crystals. The occurrence of clinopyroxene in the boundary layer is due to inward diffusion of Ca from the solvent melt to the boundary layer causing clinopyroxene saturation. Compositional profiles through the solvent and the boundary layer for a number of experiments demonstrate rapid diffusion of cations across the boundary layer – solvent interface. SiO2 diffuses outward from the boundary layer whereas CaO and Al2O3 diffuse toward the Si-enriched boundary layer melt. The rate of Al diffusion is slower under reducing conditions compared to the rates in experiments performed in air. Concentrations of FeO and MgO in the boundary layer and solvent are approximately equal indicating rapid diffusion and attainment of equilibrium despite ongoing crystallisation of clinopyroxene within the boundary layer. The behaviour of Na2O and K2O is strongly affected by f O2. Under reducing conditions Na2O and K2O concentrations are approximately equal in the boundary layer and solvent indicating normal diffusion down the concentration gradient and attainment of equilibrium. Under oxidising conditions, K2O and to a lesser extent Na2O, have compositional profiles indicative of uphill diffusion likely due to their preference for more polymerised Si- and Al-rich melts. Under reduced conditions Al-enrichment in the boundary layer melt is not as extreme and uphill diffusion did not occur. The composition of the solvent melt after the experiments indicates that it was contaminated by the boundary layer by convective mixing due to the onset of hydrodynamic instabilities brought on by density and viscosity contrasts between the two melts. Despite using a wide variety of solvent melt compositions we find that the boundary layer melts converge toward a common composition at high SiO2 contents. The composition of glass generated by orthopyroxene dissolution at 1 atmosphere is similar in many respects to Si-rich glass found in many orthopyroxene-rich mantle xenoliths that have been attributed to high pressure in situ processes including mantle metasomatism. The results of this study suggest that at least some Si-rich melts are likely to have formed by dissolution of xenolith orthopyroxene at low pressure possibly by their Si-undersaturated host magmas.